ENLIGHTENING THE FEELING OF THE MOTHERLAND IN FOREIGN LANGUAGES - Mavlanova Dildora Saidnazarovna (Web of Journals Publishing, 2023)
Enlightening the feeling of the Motherland in foreign languages is a topic that emphasizes the importance of showcasing the essence and beauty of one's homeland to people from different cultures and backgrounds. By conveying the unique attributes, values, and cultural heritage of a country, individuals can create a deeper understanding and appreciation for their motherland. This not only strengthens cultural ties but also fosters mutual respect and global integration.
Keywords: Cultural immersion program, language exchange programs, motherland, diplomatic initiatives.